2006
DOI: 10.1080/00016340600697652
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety during pregnancy and six months postpartum: a follow‐up study

Abstract: Depression and anxiety appear to be less common postpartum than during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
175
2
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(202 citation statements)
references
References 27 publications
16
175
2
9
Order By: Relevance
“…Consistent with the extant literature, we found an association between antenatal major depression and a previous history of depression 5,6,7,14,18,19,27 as well as previous psychiatric treatment 10, 23,24 . Since major depressive disorder is often a recurrent condition, it is not surprising that a prior depressive episode is a significant risk factor for depression during pregnancy.…”
Section: Factorsupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with the extant literature, we found an association between antenatal major depression and a previous history of depression 5,6,7,14,18,19,27 as well as previous psychiatric treatment 10, 23,24 . Since major depressive disorder is often a recurrent condition, it is not surprising that a prior depressive episode is a significant risk factor for depression during pregnancy.…”
Section: Factorsupporting
confidence: 79%
“…The lower prevalence in these countries might have resulted from high quality antenatal care, better nutrition during pregnancy, and less stressful life events such as financial difficulties 58,59 . Some studies in developed countries show rates in excess of 20% 6,9,15,20,23,24,60,61,62 . These findings could be explained by the use of screening questionnaires rather than diagnostic interviews.…”
Section: Factormentioning
confidence: 99%
See 1 more Smart Citation
“…(9) There are still other studies which have evaluated for the prevalence of psychiatric morbidity among antenatal women and their estimates range from 15% to 29%. (10)(11)(12)(13)(14)(15)(16)(17)(18) The wide variation in the prevalence of depression and anxiety could be due to the different scales used in various studies. The figures of 66% (women who reported having one or more mental health problem), 64% (women found to have clinically significant depression) and 46% (women found to have clinically significant anxiety) are significantly higher than those reported in the literature that was reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies establishing the prevalence of anxiety disorders in the perinatal period were identified (Table 7 [ 42,97,128,[206][207][208][209][210][211][212][213][214] In addition to the studies listed in Table 7, a number of studies have looked specifically at the incidence of postnatal PTSD with childbirth specified as the traumatic event [207,212,[215][216][217][218]. These studies, assessing for childbirth-specific PTSD occurring anywhere from 4 weeks to 1 year postpartum, found an incidence ranging from 0 to 6.9% with a mean of 3.8%.…”
Section: Anxiety Disordersmentioning
confidence: 99%